PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023 - Khafi Nugraha Iskandar; Nyoman Ari Surya Darmawan (Vokasi : Jurnal Riset Akuntansi, 2025)
The goal of this research was to analyze whethere there are affects of firm size, firm growth, and dividend policy towards firm value. This research is done with quantitive method. The research uses secondary data taken form the IDX official website. The total of sample used in this research are 15 firm of property sector that are registered to the stock exchange during the periode of 2021-2023. The sample were chosen through the purposive sampling method. The data were analyzed using multiple regression analyse with the help of SPSS 31. The result of this research show that firm size, firm growth, and dividend policy are not affecting positively towards firm value.